Effect of peroxide bleaching on the biaxial flexural strength and modulus of bovine dentin - Carvalho, Adriana Oliveira; Ayres, Ana Paula Almeida; de Almeida, Letícia Cunha Amaral Gonzaga; Briso, André Luiz Fraga; Rueggeberg, Frederick Allen; Giannini, Marcelo (European Journal of Dentistry, 2015)
Objective: This study evaluated the effects of carbamide peroxide and hydrogen peroxide on the biaxial flexural strength and flexural modulus of bovine dentin. Materials and Methods: Thirty coronal dentin disks (0.5 mm thick × 6.0 mm diameter) were prepared from bovine teeth. The disks were randomly divided into three groups (n=10): A control group (unbleached), a group bleached with 10% carbamide peroxide (8 h at 37°C), and a group bleached with 38% hydrogen peroxide (three 10 min applications at 37°C). The specimens were tested in a biaxial flexural apparatus held in a universal testing machine at 1.27 mm/min until failure occurred, and the biaxial mechanical properties were calculated. For each test parameter, the data were statistically analyzed by Fisher's PLSD test (predetermined ⍺ = 0.05). Results: The group bleached with 38% hydrogen peroxide demonstrated significantly lower flexural strength than the unbleached control group. Hydrogen peroxide treatment resulted in a significantly lower flexural modulus compared with the control group and with carbamide peroxide bleaching. Conclusion: Exposure of dentin to hydrogen peroxide significantly reduced both the flexural strength and the flexural modulus compared with the no-treatment control, whereas exposure to carbamide peroxide did not significantly affect either parameter.
Keywords: Biaxial flexural strength; bleaching; carbamide peroxide; dentin; flexural modulus; hydrogen peroxide